Associations of Longitudinal Fetal Growth Patterns With Cardiometabolic Factors at Birth - Huang, Jia-Shuan; Chen, Qiao-Zhu; Zheng, Si-Yu; Ramakrishnan, Rema; Zeng, Ji-Yuan; Zhuo, Can-Peng; Lai, Yu-Mian; Kuang, Ya-Shu; Lu, Jin-Hua; He, Jian-Rong; Qiu, Xiu (Frontiers in Endocrinology, 2021)
Background Birth weight is associated with cardiometabolic factors at birth. However, it is unclear when these associations occur in fetal life. We aimed to investigate the associations between fetal growth in different gestational periods and cord blood cardiometabolic factors. Methods We included 1,458 newborns from the Born in Guangzhou Cohort Study, China. Z-scores of fetal size parameters [weight, abdominal circumference (AC), and femur length (FL)] at 22 weeks and growth at 22–27, 28–36, and ≥37 weeks were calculated from multilevel linear spline models. Multiple linear regression was used to examine the associations between fetal growth variables and z-scores of cord blood cardiometabolic factors. Results Fetal weight at each period was positively associated with insulin levels, with stronger association at 28–36 weeks (β, 0.31; 95% CI, 0.23 to 0.39) and ≥37 weeks (β, 0.15; 95% CI, 0.10 to 0.20) compared with earlier gestational periods. Fetal weight at 28–36 (β, −0.32; 95% CI, −0.39 to −0.24) and ≥37 weeks (β, −0.26; 95% CI, −0.31 to −0.21) was negatively associated with triglyceride levels, whereas weight at 28–36 weeks was positively associated with HDL levels (β, 0.12; 95% CI, 0.04 to 0.20). Similar results were observed for AC. Fetal FL at 22 and 22–27 weeks was associated with increased levels of insulin, glucose, and HDL. Conclusions Fetal growth at different gestational periods was associated with cardiometabolic factors at birth, suggesting that an interplay between fetal growth and cardiometabolic factors might exist early in pregnancy.